2008
DOI: 10.1111/j.1365-2710.2001.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac natriuretic peptides - hope or hype?

Abstract: In recent years, biomedical science has witnessed the emergence of peptide biochemicals as significant topics of research. Some of these peptides are of little potential clinical use, while others, of which cardiac natriuretic peptides are an example, appear to be promising. This particular group of peptides (i.e. ANP, BNP and CNP) shows promising diagnostic as well as therapeutic potential for various pathological conditions. In the case of acute myocardial infarction, these peptides have significant diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Natriuretic peptides have been used as markers of heart disease based on the observation that they are involved in the activation of the cyclic guanylate cyclase system as a counterregulatory mechanism in heart failure, probably with increased cardiac wall stress as the trigger mechanism. 27,28 Natriuretic peptides have also been correlated with hemodynamic parameters and prognosis in patients with heart failure. 29,30 In pulmonary hypertension, NT-proBNP has been correlated to the hemodynamics and to the acute response to nitric oxide.…”
Section: Article In Pressmentioning
confidence: 99%
“…Natriuretic peptides have been used as markers of heart disease based on the observation that they are involved in the activation of the cyclic guanylate cyclase system as a counterregulatory mechanism in heart failure, probably with increased cardiac wall stress as the trigger mechanism. 27,28 Natriuretic peptides have also been correlated with hemodynamic parameters and prognosis in patients with heart failure. 29,30 In pulmonary hypertension, NT-proBNP has been correlated to the hemodynamics and to the acute response to nitric oxide.…”
Section: Article In Pressmentioning
confidence: 99%
“…A human atrial natriuretic peptide (hANP) preparation, carperitide, was developed and has been used mainly for treatment of heart failure because it improves preload and afterload by diuresis 2,3 and vasodilatation. [4][5][6] In the past 25 years, studies have revealed the role of ANP in cardiovascular endocrinologic systems and elucidated the details of its metabolism. It has been demonstrated to exert various effects, including inhibition of reninangiotensin, myocardial hypertrophy, and fibrosis.…”
mentioning
confidence: 99%
“…The cardiac natriuretic peptides have been actively researched over the past two decades 1,2 . Three types of natriuretic peptides have been described in Anaesthesia and Intensive Care, Vol.…”
Section: Overviewmentioning
confidence: 99%